2019
DOI: 10.3390/plants8100389
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Deficiency Effects on Pigments, Photosynthesis and Photosynthetic Electron Transport of Leaves, and Nutrients of Leaf Blades and Veins in Citrus sinensis Seedlings

Abstract: Citrus sinensis seedlings were irrigated with nutrient solution at a concentration of 0 (Mg-deficiency) or 2 (Mg-sufficiency) mM Mg (NO3)2 for 16 weeks. Mg-deficiency-induced interveinal chlorosis, vein enlargement and corkiness, and alterations of gas exchange, pigments, chlorophyll a fluorescence (OJIP) transients and related parameters were observed in middle and lower leaves, especially in the latter, but not in upper leaves. Mg-deficiency might impair the whole photosynthetic electron transport, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 66 publications
(155 reference statements)
8
47
2
Order By: Relevance
“…We observed that ALA-treated plants had more active PS II reaction centers (estimated as an increase in RC/ABS) than untreated plants at all N levels. The higher RC/ABS implies that either the active PS II reaction centers were more numerous or the apparent antenna size was smaller [38,50]. In this study, the increase in active PS II reaction centers in ALA-treated plants was supported by an increase in the active reaction centers per excited cross-section (RC/CSo) and a decrease in the closure rate of reaction centers (Mo).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…We observed that ALA-treated plants had more active PS II reaction centers (estimated as an increase in RC/ABS) than untreated plants at all N levels. The higher RC/ABS implies that either the active PS II reaction centers were more numerous or the apparent antenna size was smaller [38,50]. In this study, the increase in active PS II reaction centers in ALA-treated plants was supported by an increase in the active reaction centers per excited cross-section (RC/CSo) and a decrease in the closure rate of reaction centers (Mo).…”
Section: Discussionmentioning
confidence: 60%
“…ALA-treated plants exhibited N-dosage-specific effects on PS II activity, as indicated by the appearance of three feature peaks at all N levels ( Figure 3 d–f). The ΔK peak is an important feature of serious nutrient deficiency, as reported in radishes [ 38 ], citrus [ 50 ], maize and tomatoes [ 52 ], and beans [ 53 ]. The appearance of a positive ΔK peak suggests that the oxygen-evolving complex (especially the Mn complex on the PS II donor side) was inactivated and the antenna complexes were more connected, possibly due to improper membrane organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, carboxymethyl cellulose hydrogel is known to facilitate nutrient availability in the rhizosphere, enhancing not only nitrogen uptake, but in particular the absorption of important bivalent ions by the plant [ 43 ]. For example, magnesium (Mg 2+ ) is the central atom in the tetrapyrrole ring of chlorophyll molecules and can act as an activator of more than 300 enzymes, thus playing a key role in various physiological and biochemical processes, including chlorophyll biosynthesis and photosynthesis [ 44 ]. In addition, manganese (Mn 2+ ) is necessary for chlorophyll synthesis, but above all, it plays a key role in the oxygen evolving complex (OEC) of photosystem II, since four atoms of Mn 2+ are required to split water [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gas exchange was measured with a CIARS-2 portable photosynthesis system (PP systems, Herts, UK) at a controlled light intensity of~1000 µmol m −2 s −1 and a controlled CO 2 concentration of 380 µmol mol −1 between 9:30 and 12:30 a.m. on a sunny day [79].…”
Section: Measurements Of Plant Dw and Leaf Gas Exchange And Cu Concementioning
confidence: 99%